Experimental study on ultra-high performance concrete with high fire resistance under simultaneous effect of elevated temperature and impact loading. (April 2019) - Liang, Xiangwei; Wu, Chengqing; Yang, Yekai; Li, Zhongxian
Abstract: Fire is a big risk to buildings and structures, posing a great threat to human lives. In this study, a newly developed ultra-high performance concrete (UHPC) was investigated experimentally. Quasi-static compression tests were conducted after the UHPC was first exposed to a high temperature, i.e. 200, 400, 600, 800 or 1000 °C, and then cooled down to room temperature, while dynamic tests were carried out under combined effect of a high temperature, i.e. 200, 400, 600, or 800 °C, and impact loading. The dynamic tests were done both at high temperatures and after cooling down and comparisons were made between these two scenarios. Based on the tests on this UHPC, mechanical and physical characteristics under the combined effect were studied. Besides, explosive spalling was analysed. It was interesting to find polypropylene (PP) fibre could play a negative role in preventing explosive spalling between 320 and 380 °C.